SISTEM INFORMASI MONITORING OUTPUT ASSEMBLY BERBASIS WEB DI CLEANROOM DENGAN METODE SCRUM - Nesa Novantika; Muhammat Rasid Ridho (Universitas Putera Batam, 2026)
The development of manufacturing industries operating in cleanroom environments requires a production monitoring system that is accurate, fast, and well integrated. Manual monitoring of output assembly using paper forms or spreadsheets often leads to delays in information delivery, data recording errors, and difficulties in decision making. These limitations are critical because cleanroom production processes demand high accuracy and strict control. This study aims to design and develop a web-based output assembly monitoring information system that provides real-time and structured production data. The research applies a Research and Development (R&D) approach using the Scrum software development method. Research stages include problem identification, literature review, system requirements analysis, system design, prototype development, and system testing. The system is developed using web-based technology with a centralized database to support data input, processing, and information presentation. The results show that the proposed system improves information accessibility, minimizes data recording errors, and provides real-time visualization of production performance through a monitoring dashboard. In conclusion, the developed system effectively supports output assembly monitoring in cleanroom environments and enables faster and more accurate production decision making.